Effects of Epibiotic Diatoms on the Productivity of the Calanoid Copepod Acartia tonsa (Dana) in Intensive Aquaculture Systems - Pan, Yen-Ju; Wang, Wei-Lung; Hwang, Jiang-Shiou; Souissi, Sami (Frontiers in Marine Science, 2021)
We evaluated here the effects of the epibiotic diatom Tabularia sp. on the productivity of the calanoid copepod Acartia tonsa (Dana). Uninfested and intensively-infested females were cultivated individually for egg production assessment. Intensively-infested females appeared to have a significantly-lower egg production (5.0 to 9.0 eggs/female/d) than uninfested females (22.0 to 26.0 eggs/female/d) during 5 consecutive days. Effects of culture densities on diatom epibiosis were investigated in 9 L cultures at three different densities (200, 400 and 600 ind. L-1). A culture at higher volume (250 L) and lowest density (200 ind. L-1) was carried out to test the effect of culture volume on diatom epibiosis. The infestation ratio (%), infestation intensity (ratio of surface diatom coverage levels, classified as levels 0 to 3) and daily egg harvest rate (number of harvested eggs per day per liter) were evaluated among the four culture groups. At the lower culture volume (9 L), the copepods had higher infestation ratios (53.69 - 60.14%) and intensity (high ratios at level 2 and 3) when the densities were increased from 200 ind./L to 400 and 600 ind./L. Although egg harvest increased with increasing culture density, it seemed that the diatom-infested A. tonsa population may reach a saturated egg production when the density was higher than 400 ind./L. Nevertheless, the copepods showed a similar infestation ratio (36.17% and 35.32%) and infestation intensity (higher ratios at levels 0 and 1) when cultivated at the same density (200 ind./L) but in two different tank volumes (250 L and 9 L). This study reports for the first time the adversity of the epibiotic diatom Tabularia sp. to intensive cultures of the copepod A. tonsa, and indicates that the prevalence of diatom-copepod epibiosis is density-dependent.